Analyzing the Impact of Electronic Medical Record Implementation on Net-Benefit Using HOT-FIT - Rizqi Satria Andhika Gusni; Alih Germas Kodyat; Laila Ulfa (GLOBAL HEALTH SCIENCE GROUP, 2026)
This study aims to analyze the impact of Electronic Medical Records (EMR) implementation on the hospital’s Net Benefit using the HOT-Fit model approach, which includes the Human, Organization, and Technology components. The research was focused on the Outpatient Unit of RSB TK. III Ambon, involving 232 employees directly or indirectly involved in the EMR system implementation. A non-experimental quantitative approach with a cross-sectional correlational design was applied. Data were collected using questionnaires and analyzed through bivariate analysis using the Chi-Square test and multivariate analysis using logistic regression with the backward conditional method. The results indicate that all three HOT components Human, Organization, and Technology have a significant relationship with Net Benefit (p-value < 0.05). The calculated Prevalence Odds Ratio (POR) shows that the Human factor has a POR of 49.54, the Organization factor has 84.46, and the Technology factor has 60.00. The coefficient of determination (R²) is 0.744, meaning 74.4% of the variation in Net Benefit can be explained by the HOT variables, while the remaining 25.6% is explained by other factors outside the model. Multivariate analysis revealed that the Organization factor is the most dominant variable, with the highest odds ratio of 22.813 at a 95% confidence level and a significant p-value < 0.05. Furthermore, the Human factor was identified as a confounding variable in the relationship. It is recommended that the hospital enhance user training on system features, optimize EMR technical performance, and strengthen education and monitoring of data completeness and accuracy. Additionally, periodic and practical training tailored to each unit’s needs should be implemented, along with continuous post-training technical support. From the technological aspect, improvements in network infrastructure, provision of backup systems, and partnerships with IT service providers are necessary for regular maintenance and user support.